CRNDE: an oncogenic long non-coding RNA in cancers - Ya Lu; Huanhuan Sha; Xun Sun; Yuan Zhang; Yang Wu; Junying Zhang; Hui Zhang; Jianzhong Wu; Jifeng Feng (Cancer Cell International, 2020)
Abstract Colorectal neoplasia differentially expressed (CRNDE) is a long non-coding RNA which has been proved upregulated in various cancers. Meanwhile, CRNDE has been demonstrated to be involved in multiple biological processes of different cancers according to previous study. Moreover, recent studies suggested CRNDE might be a potential diagnostic biomarker and prognostic predictor due to its high sensitivity and specificity in cancer tissues and plasma. In this review, we summarize the biological function of CRNDE and the relevant mechanisms in cancers to establish a molecular basis for the clinical use of CRNDE in the future.